Vacuolar membrane transporters OsVIT1 and OsVIT2 modulate iron translocation between flag leaves and seeds in rice - Zhang, Yu; Xu, Yong‐Han; Yi, Hong‐Yin; Gong, Ji‐Ming (The Plant journal : for cell and molecular biology, 2012)
The plant vacuole is an important organelle for storing excess iron (Fe), though its contribution to increasing the Fe content in staple foods remains largely unexplored. In this study we report the isolation and functional characterization of two rice genes OsVIT1 and OsVIT2, orthologs of the Arabidopsis VIT1. Transient expression of OsVIT1:EGFP and OsVIT2:EGFP protein fusions revealed that OsVIT1 and OsVIT2 are localized to the vacuolar membrane. Ectopic expression of OsVIT1 and OsVIT2 partially rescued the Fe2+‐ and Zn2+‐sensitive phenotypes in yeast mutant Δccc1 and Δzrc1, and further increased vacuolar Fe2+, Zn2+ and Mn2+ accumulation. These data together suggest that OsVIT1 and OsVIT2 function to transport Fe2+, Zn2+ and Mn2+ across the tonoplast into vacuoles in yeast. In rice, OsVIT1 and OsVIT2 are highly expressed in flag leaf blade and sheath, respectively, and in contrast to OsVIT1, OsVIT2 is highly responsive to Fe treatments. Interestingly, functional disruption of OsVIT1 and OsVIT2 leads to increased Fe/Zn accumulation in rice seeds and a corresponding decrease in the source organ flag leaves, indicating an enhanced Fe/Zn translocation between source and sink organs, which might represent a novel strategy to biofortify Fe/Zn in staple foods.